2015 Portland International Conference on Management of Engineering and Technology (PICMET) 2015
DOI: 10.1109/picmet.2015.7273196
|View full text |Cite
|
Sign up to set email alerts
|

Technology readiness levels at 40: A study of state-of-the-art use, challenges, and opportunities

Abstract: The technology readiness level (TRL) scale was introduced by NASA in the 1970s as a tool for assessing the maturity of technologies during complex system development. TRL data have been used to make multi-million dollar technology management decisions in programs such as NASA's Mars Curiosity Rover. This scale is now a de facto standard used for technology assessment and oversight in many industries, from power systems to consumer electronics. Low TRLs have been associated with significantly reduced timeliness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…So even that the technology is mature, using this technology in new applications may be challenging, and the TRL scale usually does not represent the challenge of integrating the technology in a space system. Olechowski, Eppinger and Joglekar (2015) investigated the use of the TRL scale in different industrial sectors through interviews and analyzes on industry standards and organizational guidelines. These authors (Olechowski et al, 2015) found that the TRL scale is widely used in different complex systems industries and identified fifteen challenges to improve the TRL scale utilization, categorized in three topics: system complexity, planning and review, and assessment validity.…”
Section: IImentioning
confidence: 99%
See 3 more Smart Citations
“…So even that the technology is mature, using this technology in new applications may be challenging, and the TRL scale usually does not represent the challenge of integrating the technology in a space system. Olechowski, Eppinger and Joglekar (2015) investigated the use of the TRL scale in different industrial sectors through interviews and analyzes on industry standards and organizational guidelines. These authors (Olechowski et al, 2015) found that the TRL scale is widely used in different complex systems industries and identified fifteen challenges to improve the TRL scale utilization, categorized in three topics: system complexity, planning and review, and assessment validity.…”
Section: IImentioning
confidence: 99%
“…Olechowski, Eppinger and Joglekar (2015) investigated the use of the TRL scale in different industrial sectors through interviews and analyzes on industry standards and organizational guidelines. These authors (Olechowski et al, 2015) found that the TRL scale is widely used in different complex systems industries and identified fifteen challenges to improve the TRL scale utilization, categorized in three topics: system complexity, planning and review, and assessment validity. Subsequently, Tomaschek, Olechowski, Eppinger and Joglekar (2016) conducted a survey with TRL scale practitioners in different industries worldwide to identify, among the fifteen identified challenges, which were the most priority challenges.…”
Section: IImentioning
confidence: 99%
See 2 more Smart Citations
“…Its application was mostly to manage and monitor the risk of acquisition of technologies in different stages of development [7,8]. However, the adaptation of the TRL in different industries, encountered challenges in terms of its integration and connectivity, scope of TRL assessment, product road mapping or imprecision of the scales [9,10].…”
Section: Introductionmentioning
confidence: 99%